The Role of Renewable Energy in Supporting Economic Growth in North Africa from 2000 to 2023 - Ibrahim, Ayman Salahedeen; Ismaeel, Waleid Mahmoud (المجلة العلمية للدراسات والبحوث المالية والتجارية: علمية محكمة., 2025)
This study examines the role of renewable energy in supporting economic growth in North Africa, focusing on Egypt, Libya, Tunisia, Algeria, and Morocco. using panel data from 2000 to 2023, we employ a generalized method of moments (GMM) approach and granger causality tests to analyze the relationship between renewable energy adoption and economic growth. our findings reveal a significant positive impact of renewable energy on economic growth in the region, with a 1% increase in renewable energy share associated with a 0.1523% increase in economic growth. granger causality tests indicate a unidirectional causality from renewable energy to economic growth, supporting the "growth hypothesis" in the energy-growth nexus literature. the study also considers the effects of foreign direct investment, human capital, trade openness, inflation, and governance on economic growth. our results suggest that policies promoting renewable energy adoption could yield dual benefits of fostering sustainable development and stimulating economic growth in north African countries. these findings have important implications for policymakers in the region, highlighting the potential of renewable energy as a catalyst for economic development. تتناول هذه الدراسة دور الطاقة المتجددة في دعم النمو الاقتصادي في شمال أفريقيا، مع التركيز على مصر وليبيا وتونس والجزائر والمغرب. وذلك باستخدام بيانات من عام ۲۰۰۰ إلى عام ۲۰۲۳، باستخدام نهج طريقة اللحظات المعممة واختبارات السببية لجرانجر لتحليل العلاقة بين الطاقة المتجددة والنمو الاقتصادي. تكشف نتائجنا عن تأثير إيجابي كبير للطاقة المتجددة على النمو الاقتصادي في المنطقة، حيث ارتبطت زيادة بنسبة 1% في حصة الطاقة المتجددة بزيادة بنسبة ٠,١٥٢٣% في النمو الاقتصادي. تشير اختبارات السببية لجرانجر إلى سببية أحادية الاتجاه من الطاقة المتجددة إلى النمو الاقتصادي، مما يدعم "فرضية النمو" في أدبيات العلاقة بين الطاقة والنمو. كما قام الباحثان بدراسة آثار الاستثمار الأجنبي المباشر ورأس المال البشري وانفتاح التجارة والتضخم والحوكمة على النمو الاقتصادي. وأشارت نتائجنا إلى أن السياسات التي تعزز تبني الطاقة المتجددة يمكن أن تحقق فوائد مزدوجة تتمثل في تعزيز التنمية المستدامة وتحفيز النمو الاقتصادي في دول شمال أفريقيا. ولهذه النتائج آثار مهمة على صناع السياسات في المنطقة، إذ تسلط الضوء على إمكانات استخدام الطاقة المتجددة كمحفز للتنمية الاقتصادية.